Reduction of Peak-to-Average Power Ratio of OFDM System Using Triangular Distribution Based Modified Companding Scheme. Issue 5 (3rd September 2018) - Bhattacharjee, Subhankar; Rakshit, Mahua; Sil, Sanjib; Chakrabarti, Amlan
ABSTRACT: Orthogonal frequency division multiplexing (OFDM) is an attractive multicarrier modulation technique, which is widely introduced in the present as well as future broadband wireless communication systems due to high data rate, high spectral efficiency, and robustness to the multipath fading channel. Despite its popularity, OFDM system suffers from the critical drawback of large peak-to-average power ratio (PAPR) of the transmitted signal, which may lead to undesired spectral re-growth, poor power efficiency, and overall performance degradation. In this paper, we propose an efficient non-linear companding transform (NCT) technique for reducing the PAPR of OFDM signals. Our proposed scheme coined as triangular distribution (TR) based companding offers an improved bit error rate (BER), better design flexibility, and more degrees of freedom while reducing PAPR effectively compared to the other existing companding schemes. The PAPR reduction performance of our proposed scheme for the different modulation approaches like QPSK, 4QAM, 16QAM, 32QAM, and 64QAM is also presented here. The theoretical analysis of the proposed scheme and comparative study with the existing algorithms are presented. Simulation results demonstrate that our proposed companding scheme can substantially outperform the existing NCT techniques in terms of PAPR reduction, BER performance, and bandwidth efficiency for each of the modulation approaches under different noisy channel conditions.